Clinical and imaging features of primary thyroid MALT lymphoma - Xiao, Liming; Zhao, Ziyi; Zhou, Li; Yan, Jiao; Luo, Danling; Liu, Fucen; Zhou, Qiaolin; Huang, Dan (Frontiers in Oncology, 2025)
Primary thyroid lymphoma is a rare hematologic malignancy of the thyroid gland, accounting for approximately 5% of all malignant thyroid tumors. The most common pathological type is B-cell-derived non-Hodgkin’s lymphoma, mainly diffuse large B-cell lymphoma, followed by mucosa-associated lymphoid tissue lymphoma and mixed types. The clinical and radiographic characteristics of primary thyroid lymphoma are non-specific, often leading to misdiagnosis as thyroiditis and a delay in treatment. A 60-year-old woman was referred to our hospital with neck swelling that had persisted for a week. Histopathological findings of a thyroid biopsy revealed mucosa-associated lymphoid tissue lymphoma. Bone marrow examination revealed atypical lymphocytes on myelograms. [18F]FDG PET/CT images showed increased [18F]FDG uptake in both lobes of the thyroid gland and the cervical lymph nodes. The patient was diagnosed with stage IV primary thyroid mucosa-associated lymphoid tissue lymphoma. The patient subsequently received four cycles of R-CEOP chemotherapy and remained under follow-up. Due to the rarity of this case, we conducted a systematic literature review to better understand the disease and improve timely diagnosis and treatment.